Community Participation in Tourism Development in the Village: Examining from Subang District, Indonesia - Yerik Afrianto Singgalen; Astuti Kusumawicitra Laturiuw; Titis Puspitarini; Zsarin Astri Puji Insani (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to identify the potential and readiness of the Ponggang community to develop tourism villages. Considering the implications of development on the transformation of people's livelihoods have a dual effect in various sectors of the economy, this research is necessary to obtain comprehensive and contextual information. The research method used is qualitatively interpretive through a case study approach in Ponggang Village, Serang Panjang District, Subang, West Java. The data collection techniques are in-depth interviews, observations, and document studies. In-depth discussions of key informants are needed to identify stakeholder perceptions. This Research discussed a Ladder of Participation Theory by Arnstein. The findings of this study reveal that the pattern of Ponggang communities’ social interaction is attached to the action of cooperation. It becomes a socio-cultural characteristic that affects the process of infrastructure development. It indicates that social ties strengthen communal norms and foster a sense of belonging to development programs. At the same time, it also triggered a positive response that was expressed in the sincere expression of the community to actively participate in partnership programs with the government and academics institution to develop the potential of natural resources, human resources, and cultural resources as a tourism destination. Based on the form and level of participation stated by Arnstein, the structure of the involvement relevant to the context of the Ponggang community has increased from informing, consultation, and placation to the steps of partnership and delegated power. Thus, there is a potential to achieve the stage of citizen power and become economically independent through tourism development.